PROGRAM EDUKASI ANEMIA UNTUK SISWA SMP: “KENALI ANEMIA, JAGA SEHATMU!” - Srikandi, Uci Meutia; Yolanda, Tanaya; Rahmadani, Zahra Dwita Putri; Simanungkalit, Nur Aysah (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
Anemia is a common health issue among adolescents, primarily caused by iron deficiency. This condition can negatively impact students' academic performance, physical growth, and psychological well-being. The program "Know Anemia, Maintain Your Health!" was conducted as a community service initiative to raise awareness about anemia among students. The activity took place at MTsN 7 Aceh Barat on November 16, 2024, involving 25 ninth-grade students. The methods included delivering educational materials using PowerPoint presentations, interactive discussions, and evaluations through post-tests. Results showed that 80% of students improved their understanding of anemia, particularly in identifying its symptoms and preventive measures, such as consuming iron-rich foods and maintaining a healthy diet. The main supporting factor was the full support of the school principal, while the limiting factor was the time constraints, which caused some students to lose focus. This program successfully increased students' awareness of anemia. Interactive and participatory health education proved to be an effective strategy for delivering essential information to adolescents.